Precise CRISPR/Cas9 editing of the NHE1 gene renders chickens resistant to the J subgroup of avian leukosis virus - Koslová, Anna; Trefil, Pavel; Mucksová, Jitka; Reinišová, Markéta; Plachý, Jiří; Kalina, Jiří; Kučerová, Dana; Geryk, Josef; Krchlíková, Veronika; Lejčková, Barbora; Hejnar, Jiří (Proceedings of the National Academy of Sciences of the United States of America, 2020)
Avian leukosis virus subgroup J (ALV-J) is an important concern for the poultry industry. Replication of ALV-J depends on a functional cellular receptor, the chicken Na+/H+ exchanger type 1 (chNHE1). Tryptophan residue number 38 of chNHE1 (W38) in the extracellular portion of this molecule is a critical amino acid for virus entry. We describe a CRISPR/Cas9-mediated deletion of W38 in chicken primordial germ cells and the successful production of the gene-edited birds. The resistance to ALV-J was examined both in vitro and in vivo, and the ΔW38 homozygous chickens tested ALV-J-resistant, in contrast to ΔW38 heterozygotes and wild-type birds, which were ALV-J-susceptible. Deletion of W38 did not manifest any visible side effect. Our data clearly demonstrate the antiviral resistance conferred by precise CRISPR/Cas9 gene editing in the chicken. Furthermore, our highly efficient CRISPR/Cas9 gene editing in primordial germ cells represents a substantial addition to genotechnology in the chicken, an important food source and research model.
Keywords: kur domácí; Poultry Diseases; primordial germ cells; Male; virus ptačí leukózy; ptačí proteiny; odolnost vůči nemocem; Chickens; editace genu; Avian Leukosis Virus; CRISPR/Cas9 genome editing in chicken; Na+/H+ exchanger type 1; avian leukosis virus subgroup J; Avian Proteins; mužské pohlaví; ptačí leukóza; Gene Editing; nemoci drůbeže; Animals, Genetically Modified; Disease Resistance; Avian Leukosis; sodíko-vodíkový výměnný transportér 1; CRISPR-Cas Systems; Animals; ženské pohlaví; zvířata; CRISPR-Cas systémy; disease resilience in poultry; Female; geneticky modifikovaná zvířata; Sodium-Hydrogen Exchanger 1